The Influence of Risk Management Policies, Risk Management Procedures on Credit Risk Levels Through Risk Management Limits (Case Study of Banks Credit in the South Sulawesi Province Region) - Mulyana, Mulyana; Sobarsyah, Sobarsyah; Dewi, Andi Ratna Sari (Pascasarjana STIE Amkop Makassar, 2023)
Analysis of risk management policies, procedures, and limits on setting risk management limits, analysis of how these factors affect the degree of credit risk in BPRs, and analysis of how these factors affect the level of credit risk through risk management limits at BPRs in the South Sulawesi Province Region are the main objectives of this research. In order to accomplish this goal, a sample of 150 respondents management, executive officers, and staff members of rural banks in the South Sulawesi Province region were used. Data analysis techniques using SEM-Amos and questionnaires were used to collect the data. The study's findings demonstrate that risk management practices and rules actually affect how management boundaries are created. The degree of credit risk is then significantly impacted by risk management policies and practices. The degree of credit risk can be significantly impacted by the management limit settings. The mediation test's findings indicate that imposing risk management limitations can moderate the impact of risk management guidelines and practices on the degree of credit risk in BPRs in the province of South Sulawesi. Keywords: Risk management policy, risk management procedures, setting risk management limits and credit risk levels.